Demography and Short Term Functional Outcome of Soft Tissue Sarcoma Treated with Limb Salvage Surgery - Pandey, Suresh (Journal of College of Medical Sciences-Nepal, 2020)
Background: Limb salvage surgery with or without radiotherapy and/or chemotherapy is the mainstay of treatment of Soft Tissue Sarcoma (STS). Though, many studies are found regarding the demographics and result of such malignancy from other parts of the world, such data is not available from our country. This study aimed to analyze the demographic data and functional outcome of STS treated with limb salvage surgery. Methods: It is a retrospective review of 16 cases of soft tissue sarcoma of extremities and trunk managed with limb salvage surgery followed by adjuvant radiotherapy and/or chemotherapy in indicated cases from 2012 to 2017. Demographic data and functional score after 2 years of surgery were analysed and presented. Results: There were 14 male and 2 female cases of STS with mean age of 32.88 years. The most common STS was liposarcoma (37.5%) followed by rhabdomyosarcoma (25%) and synovial sarcoma (18.8%). Extremity and lower limb were the most common sites. Mean MSTS functional score at the last follow up was 24.56 (81.83%) with range from 19-29 (63.33%-96.66%). There were good to excellent results in 13 cases (81.25%) and moderate result in 3 cases (18.75%) according to MSTS functional score. There was positive correlation of MSTS with age, radiotherapy, chemotherapy and negative correlation with grade of tumor. Conclusions: This study showed good to excellent functional results in 81.25% of cases as per Musculoskeletal Tumor Society Score (MSTS) with positive correlation with radiotherapy, chemotherapy, age and negative correlation with grade of tumor.